O uso de um livro-jogo como recurso para o ensino de física - Silva Júnior, Edézio Souza da (2022)
Through a literature review, we revisited some problems related to Physics Teaching to better understand the current difficulties in its realization and to contribute to the production of a Game Book and an analysis of its functioning in the classroom. Observing the Game Book's behavior dynamics through data collection with High School’s last grade students during the COVID-19 pandemic, we added to Physics Teaching a breath of traditional teaching and learning methods, since these permeate a large part of the founded problems. The Game Book brings a more playful way to the topics covered, contributing to a better fixation of the contents by the students. Guided by materials consulted in a bibliographic survey, the research details the functioning of this book with the students, analyzing important points of the functioning of teaching using this type of tool, showing data of effectiveness and acceptance by the students.